Zionism : the real enemy of the jews. the false messiah - Hart, Alan. (karchi : Paramount Pub., 2009)
The False Messiah is the first volume in the series, ZIONISM: THE REAL ENEMY OF THE JEWS, an epic journey through the propaganda lies and documented truth of history by a seasoned reporter who interviewed and was in the good graces of the major players on all sides. Alan Hart has given an honest expression of the needs, motives and dilemmas faced by all parties. He offers many unique insights into the formative events in this region and the evolution of relations within and between the Israeli, Arab, US, UK and European leadership. This is the first book to put the struggle for Palestine into its global context--to show how all the pieces of a complicated jig-saw puzzle fit together. It's also the first ever account of events to address the motives, needs, and dilemmas faced by all sides: diaspora Jews' real fear of Holocaust II; the Palestinian right to justice and self-determination; the legitimate anger of the Arab masses at American support for Zionism right or wrong; and the inevitable corruption and repression of the regimes of the existing Arab Order who, fearing harsher Israeli assaults, have tried to contain them. "Hart s readable account of history, his obviously erudite analysis and his ability in bringing the factual conflict to life on the page ensures the reader's interest is unwavering throughout. His passion and empathy with both sides is apparent. For the Jews, the unspeakable fear of another Holocaust due to Zionist manipulation and tyranny; and for the Arabs and Muslims, the anger and humiliation they are feeling every day that Palestine is being torn apart." -- Samira Quraishy, researcher, Islamic Human Rights Commission "Hart's book is a good act, a brave act for someone from British state media. He says he has to live with himself, and it is obvious this book comes from a place of integrity. Volume One: The False Messiah augurs well for the rest of the series." -- KIM PETERSEN, Dissident Voice "These two volumes are a vital exposition of Zionist history and its interface with diplomacy and the Israel-Arab conflict, up until the assassination of President Kennedy. Alan Hart promises another volume, perhaps two, and one looks forward to their publication.... an essential understanding of what happened in the struggle for Israel-Palestine and of the role of Zionism in this sad story." -- REUEL AMDUR, The Canadian Charger, January 27, 2010.
Vol. 1. The false Messiah -- Vol. 2.David Becomes Goliath.